Chronicling the Shifts: Using the Body Lens to Analyze Policy for High Need Women Offenders - Durrell, Jennifer E A (Université d'Ottawa / University of Ottawa, 2011)
This thesis uses an exploratory case study design to chronicle the shifts, recognition, and implementation of programs, tools and policies designed for high need federally sentenced women in Canada that were created after 1990, in accordance with or opposed to the gender specific principles outlined in the Creating Choices (1990) report. The body lens is used as an analytic tool to deconstruct eleven of the most pertinent documents regarding policy and strategy for high need women offenders that were implemented by the Correctional Service of Canada (CSC) personnel and the Office of the Correctional Investigator (OCI) over the past twenty years. Coding of a wide range of documents reveals that despite appearing to be rhetorically progressive, CSC’s attempt at creating a women-centered mental health strategy uses contradictory disciplinary techniques that control and restrain the bodies of federally sentenced women in hopes of normalizing the behaviours of high need women. The policies imposed by CSC for high need women offenders fail to make any substantial changes in women’s prison reform and resulted in a different form of regulation and control. High need women offenders are imprisoned in their own bodies.
Keywords: Creating Choices; Women Offenders; Intensive Intervention Strategy; Body Lens; High Need Women Offenders; Federally Sentenced Women